2015
DOI: 10.4163/jnh.2015.48.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Use of vitamin and mineral supplements and related variables among university students in Seoul

Abstract: Purpose: Despite the popularity of dietary supplements, little data are available on their use by university students. The purpose of this study was to examine the use of vitamin mineral supplements and to identify factors related to supplement use among university students. Methods: University students (N = 345) in Seoul were surveyed. Survey questions included descriptive demographics, types of vitamin and mineral supplements used, health related lifestyle factors, mini dietary assessment, and knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This study found that more than half of respondents have taken DSs, and out of these groups, almost half were taking the aforementioned supplements during the course of the research. This result is similar to the outcome of the KNHANES, which indicated that about 42% of Korean adults have taken a DS at least once in their life [5]. Interestingly, the most important driver of DS consumption is recommendation from family members.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This study found that more than half of respondents have taken DSs, and out of these groups, almost half were taking the aforementioned supplements during the course of the research. This result is similar to the outcome of the KNHANES, which indicated that about 42% of Korean adults have taken a DS at least once in their life [5]. Interestingly, the most important driver of DS consumption is recommendation from family members.…”
Section: Discussionsupporting
confidence: 83%
“…In the Korean context, about 42% of adults have taken a DS at least once in their lifetime, as indicated in the results of the Korean National Health and Nutrition Examination Survey in 2015 (KNHANES) [4]. The market for DSs has rapidly increased since 2009, reaching a size of US$1792 million in 2013 [5]. Vitamin or mineral products are the most frequently consumed supplements in the country [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cases of adding raw materials with efficient functions on the human body and insufficient nutrients as the social interest in the health and well-being increases [1] and the dependency on the dietary supplement has grown for the health of family members due to inflating worries about the health from increasing number of dual incomes and Westernized diet [2]. In addition, the interest in the children health grows due to social changes including increasing income of parents, growing academic achievement among parents and lowering birth rates, shifting the trend in purchasing functional products for adults to those for children and adolescents [3].…”
Section: Introductionmentioning
confidence: 99%